Fatigue analysis of metallic-plastic-metallic pipeline systems: A numerical study - Ji-Sung Lee; Wei Zeng; Martin Lambert; Timothy Hilditch; Jinzhe Gong (Results in Engineering, 2023)
Metallic (e.g., copper, steel and iron) and plastic (e.g., Polyethylene and Polyvinyl chloride) pipelines are often used in combination in water distribution networks (WDSs). The interface between a metallic pipe section and a plastic pipe section is typically associated with a significant change in hydraulic impedance (i.e., impedance mismatch). This impedance mismatch can result in significant pressure wave reflections during transient events, and multiple interfaces may induce repeated pressure waves bouncing in between. Limited studies have been conducted on the impact of these multiple wave reflections due to impedance mismatch, especially with respect to the risk of accelerated fatigue damage to the plastic pipe. The research presented in this paper investigates the pressure response of a metallic-plastic-metallic (M-P-M) pipeline system under repeated hydraulic transient events using analytical and numerical methods. The presence of additional cyclic hoop-stress loadings in the M-P-M configuration, both in frequency due to reflections and in loading magnitude due to superposition, has been demonstrated in comparison to a fully plastic pipe system under the same hydraulic transient event. The study investigates the impact of these additional loadings on the relative fatigue lifetime of the plastic section by adopting a fatigue analysis model based on the stress-life method. The results show that the plastic section in the M-P-M configuration can have a significant reduction in fatigue lifetime compared to the corresponding fully plastic configuration.